Vitamin D deficiency is not related to eating habits in children with Autistic Spectrum Disorder - Maria Pia Riccio; Gennaro Catone; Rosamaria Siracusano; Luisa Occhiati; Pia Bernardo; Emilia Sarnataro; Giuseppina Corrado; Carmela Bravaccio (AIMS Press, 2020)
Background and aims Autism Spectrum Disorder (ASD) is characterized by the impairment of communication and social interaction and by repetitive, restricted and stereotyped interests. ASD is often accompanied by comorbidities; eating disorders are frequent and imply important nutritional deficits (i.e. deficiencies of vitamins, minerals and fatty acids). Vitamin D has a critical role in neurodevelopment and serum levels in ASD are reported inadequate. A useful reference for setting up a correct diet in childhood is the food pyramid, which is inspired by the Mediterranean Diet (MD). The MD guarantees an intake of nutrients, considered optimal to maintain an adequate nutritional status. The aim of this study is to explore serum levels of Vitamin D and food habits (through MD adherence) in a sample of children with ASD and evaluate a possible correlation between these factors. Methods study participants include 91 children 47 presenting ASD and 44 healthy typically-developing (TD) subjects, as control group. We evaluated serum level of Vitamin D in both group; anthropometric parameters (weight, height, body mass index-BMI-and growth percentile) and MD adherence have been explored, in order to investigate the correlation among those data and level of Vitamin D in children with ASD. Lastly, the association between Vitamin D levels and severity of ASD symptoms has been analysed. Results and conclusion 74% of ASD group presented blood levels of Vitamin D under 30 ng/ml (normal range 30-100 ng/ml). The analysis performed showed that the two groups were significant different regards Vitamin D levels (t = 2.24, p < 0.05), according to literature. 31.9% of children with ASD presented a condition of overweight and 12.6% a condition of obesity. Adherence to the MD was low in 25.5% of cases. No significant statistical correlation has been found between Vitamin D serum levels, anthropometric parameters and the adherence to MD in the ASD group.